The Impact of The Utilization of Electronic Payment Moderated by Financial Technology Innovation on Financial Technology Payment in Indonesia - Surjadi, Julisar; Supriatna, Dicky; Debora, Debora (Diponegoro University, 2025)
Information technology is currently developing rapidly and covers many aspects of people's lives. The development of information technology also includes in the financial sector. The development of information technology in the financial sector is referred to as Financial Technology. The purpose of this study was to test and analyze The Utilization of Electronic Payment moderated by Financial Technology Innovation on Financial Technology Payment in Indonesia. The theories used in this study are the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), Electronic Payment, Financial Technology, Diffusion of Innovation Theory, and Financial Technology Payment. Diffusion of Innovation (DOI) Theory in 1962, making it one of the earliest social science theories. A theory known as